EFFECT OF SQ, HRQ, ISP AND TECHNOLOGY SOFTWARE ON ACCOUNTING INFORMATION SYSTEM EFFECTIVENESS - Dini, Siti; Desy, Desy; Fiorentina, Vanny (Jurnal Ipteks Terapan, 2022)
Background : The domestic animal feed industry encourages the livestock industry to consume meat and its processed products for the community as a source of protein. According to BPS Indonesia, feed contributes 70% of all funds for livestock production. Method : The research method is a scientific technique to obtain data with an achievement and benefit. Result : The results of the coefficient of determination test, namely the adjusted R2 value, which is 0.950, the impact of the quality of the system and human resources, individual work systems and technological sophistication have an impact on the effectiveness of AIS at PT Leong Hup Jayaindo Medan which is 95%, the remaining 5% gets the impact of the variables studied. Conclusion : Variables of system quality and human resources, individual performance systems and technological sophistication simultaneously have an impact on the effectiveness of SIA at PT Leong Hup Jayaindo Medan